On the 3rd order linear differential equation - Ley, BL Moreno-; Bonilla, J Lopez-; Tuladhar, B Man (Kathmandu University Journal of Science Engineering and Technology, 2013)
If for an arbitrary 3th order linear differential equation, non-homogeneous, we know two solutions of its associated homogeneous equation (HE), then we show how to determine the third solution of HE and the particular solution of the original equation.